An empirical study on the intervention of traditional Chinese medicine five-element music in alleviating anxiety and depression among medical students: differences in effectiveness among three different musical instruments - Lyu, Peng; Li, Xiaobing; Yao, Xiyong (Frontiers in Psychology, 2025)
BackgroundThe efficacy of Traditional Chinese Medicine (TCM) Five Elements Music in intervening anxiety and depression has been extensively validated by trials. This study employed three different instruments to perform TCM Five Elements Music interventions on medical students’ anxiety and depression, aiming to evaluate the differences in therapeutic effects and provide empirical evidence for optimizing treatment protocols.MethodsA total of 148 medical students screened via the Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) were randomly divided into an Erhu group, Guzheng group, Bamboo flute group, and a Control group (37 participants each). The three intervention groups listened to TCM Five Elements Music for 15 min daily over 2 weeks, while the Control group received no intervention. Pre- and post-intervention assessments were conducted using the SAS and SDS.ResultsExcept for the Control group, all three intervention groups showed significantly lower SDS and SAS scores post-intervention compared to pre-intervention (p < 0.01). Statistically significant differences in SDS and SAS scores were observed among the three intervention groups post-intervention (p < 0.01), with the Guzheng group demonstrating the most pronounced intervention effect.ConclusionTCM Five Elements Music effectively alleviates anxiety and depression in medical students. The therapeutic effects vary significantly across different instruments, with the Guzheng yielding the most remarkable outcomes.Clinical trial registrationThis study has been registered with the International Traditional Medicine Clinical Trial Registry (Registration No.: ITMCTR2025000818).